Spectrum of pathogenic variants and high prevalence of pathogenic BBS7 variants in Russian patients with Bardet–Biedl syndrome - Orlova, M.; Gundorova, P.; Kadnikova, V.; Polyakov, A. (Frontiers in Genetics, 2024)
Introduction Bardet–Biedl syndrome is a rare condition characterized by obesity, retinitis pigmentosa, polydactyly, development delay, and structural kidney anomalies. This syndrome has an autosomal recessive type of inheritance. For the first time, molecular genetic testing has been provided for a large cohort of Russian patients with Bardet–Biedl syndrome. Materials and methods Genetic testing was provided to 61 unrelated patients using an MPS panel that includes coding regions and intronic areas of all genes (n = 21) currently associated with Bardet–Biedl syndrome. Results The diagnosis was confirmed for 41% of the patients (n = 25). Disease-causing variants were observed in BBS1, BBS4, BBS7, TTC8, BBS9, BBS10, BBS12, and MKKS genes. In most cases, pathogenic and likely pathogenic variants were localized in BBS1, BBS10, and BBS7 genes; recurrent variants were also observed in these genes. Discussion The frequency of pathogenic and likely pathogenic variants in the BBS1 and BBS10 genes among Russian patients matches the research data in other countries. The frequency of pathogenic variants in the BBS7 gene is about 1.5%–2% of patients with Bardet–Biedl syndrome, while in the cohort of Russian patients, the fraction is 24%. In addition, the recurrent pathogenic variant c.1967_1968delinsC was detected in the BBS7 gene. The higher frequency of this variant in the Russian population, as well as the lack of association of this pathogenic variant with Bardet–Biedl syndrome in other populations, suggests that the variant c.1967_1968delinsC in the BBS7 gene is major and has a founder effect in the Russian population. Results provided in this article show the significant role of pathogenic variants in the BBS7 gene for patients with Bardet–Biedl syndrome in the Russian population.